Pengaruh Ketersediaan Teknologi Dan Disiplin Kerja Terhadap Kinerja Pegawai Melalui Motivasi Kerja Sebagai Variabel Intervening Pada Kantor Camat Tanjung Harapan Kota Solok - Rahmat Hafiz Audia; Dori Mittra Candana; Chintya Ones Charli (Jurnal Ekonomi dan Bisnis Digital, 2026)
This research is driven by the importance of optimizing employee performance in government agencies, which is influenced by factors such as discipline, technology support, and the dynamics of employee work motivation. The aim of this quantitative study is to analyze the effect of Technology Availability and Work Discipline on Employee Performance through Work Motivation as an intervening variable at the Tanjung Harapan Sub-District Office in Solok City. This study uses the entire population of 41 respondents as the research sample. Data were collected through questionnaires and analyzed using variance-based Structural Equation Modeling (SEM) through SmartPLS software. The path analysis results show that Technology Availability and Work Discipline directly have a positive and significant effect on both Work Motivation and Employee Performance, and Work Motivation also has a positive and significant effect on Employee Performance. In addition, the results of the influence test